Studies in carpal tunnel syndrome and cold intolerance - Salem-Saqer, Khaled (2008)
Carpal tunnel syndrome (CTS) presentation is usually classic but cold-related Raynaud's phenomenon (RP)-like symptoms were described in CTS and more commonly in the injured hand (HI).